Teaching English to Young Learners Practicum Program: Do Philosophical Foundations Matter? - Yuniar Diyanti; Darmiyati Zuhdi (Universitas Bengkulu, 2020)
A practicum, like any other educational practices, is supported by a set of an operating procedure or a guideline. The guideline may be in the form of a curriculum book, a syllabus, or a set of Standard Operating Procedure (SOP). A curriculum or guidelines in education carry their philosophical foundations that serve as the driving forces of the educational practice. This article aims at revealing the philosophical foundations that embody English for Young Learners' practicum program through an inferential content analysis study. The data were in the form of phrases and sentences taken from the practicum operating procedures and other relevant documents. The results showed that the most mentioned aspect of the documents was the learners’ roles. This finding led to the discovery of the philosophical foundations of the practicum which were dominated by Progressivism and followed by Social Reconstruction, Existentialism, and Religious Humanism. The findings of the study also raised the discussion on how relevant educational philosophies towards the efforts of preparing teachers in the 21st century.